1999
DOI: 10.1142/s0217732399002236
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of a Positive Vacuum Energy in a Quantum Model for Space–time

Abstract: It is shown that a previously proposed quantum model for four-dimensional space-time based on an SU(∞) generalization of anyonic superconductivity can be regarded as a discrete form of Polyakov's string theory. This suggests that in a Robertson-Walker universe there is a positive vacuum energy that is on the order of the string tension divided by square of the distance scale factor. This leads to a new type of cosmological model that, even though it resembles more an open universe than an accelerating universe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The charge carriers in these 2-dimensional planes are quasi-localized solitons, which we have called "chirons" because of the key role played by chiral currents. Soon after the chiron model was put forward as a theory of high Tc superconductivity it was realized that this theory might also be interpreted as a quantum theory of space-time [9,10]. In this theory the vacuum of space-time is pictured as arising -as in the case of high Tc superconductivity -from a KTlike condensation of self-dual and anti-self-dual chirons.…”
Section: Chiron Description Of the Critical Surface Layermentioning
confidence: 99%
“…The charge carriers in these 2-dimensional planes are quasi-localized solitons, which we have called "chirons" because of the key role played by chiral currents. Soon after the chiron model was put forward as a theory of high Tc superconductivity it was realized that this theory might also be interpreted as a quantum theory of space-time [9,10]. In this theory the vacuum of space-time is pictured as arising -as in the case of high Tc superconductivity -from a KTlike condensation of self-dual and anti-self-dual chirons.…”
Section: Chiron Description Of the Critical Surface Layermentioning
confidence: 99%
“…More recently it has been suggested that the vacuum of space-time may itself be a macroscopic quantum state [4,5]. Identifying the physical vacuum of space-time as a macroscopic quantum state is very compelling for a number of reasons, but perhaps most notably because it provides a unified explanation for both the observed cosmological vacuum energy [6] and existence of dark matter [7]. The basic idea [8] is that dark matter consists of gravitationally stable quantum dropletspreviously referred to as "dark energy stars" -whose interior is like the ordinary spacetime vacuum except that the vacuum energy density is much higher.…”
Section: Introductionmentioning
confidence: 99%